The Effect of Education on Clean and Healthy Living Behavior of Latrine Use in School-Age Children - Jawar, Martafina; Faizal, Faizal; Wanci, Risman (Omni Health Journal, 2025)
Background: The habit of urinating in a clean toilet is a common thing in PHBS. Given that many diseases are transmitted when urinating in any place, this is a healthy habit. Objective: The purpose of the research is to find out whether school-age students of SD Hasanudin Gowa use latrines or not. as a result of PHBS instruction. Methods: The research design in this study is Pre Experiment with a Pretest – Postest approach. Results: The results of the statistical test using an alternative test (Wilcoxon Test) with a value of p= 0.004 < 0.05, then Hₒwas rejected andHₐ  was accepted so that it can be concluded that there is an Effect of Education on PHBS Knowledge of Toilet Use in School-Age Children at SD Hasanudin Gowa. For this reason, it is hoped that there will be a need to increase education on student knowledge in PHBS on the use of latrines so that good student knowledge can change bad behavior for better in terms of improving healthy and clean living behavior. Conclusion: Based on the results of the study, it is concluded that there is an influence of PHBS education on the use of latrines on school-age children at SD Hasanudin Gowa. So it is recommended that every student not only knows what a healthy latrine is and PHBS for the use of clean and healthy latrines but can apply it.